Analysis of hematogones in bone marrow from acute myeloid leukaemia cases posttherapy. (2nd September 2013) - Zheng, Jine; Du, Wen; Yao, Junxia; You, Yong; Li, Weiming; He, Yanli; Li, Xiaoqing; Liu, Wei; Wu, Yaohui; Hu, Yanjie; Jin, Runming; Zou, Ping; et al.
Abstract Background Increased bone marrow (BM) hematogones (HGs) are often observed in patients with marrow regenerating status. Many studies have focused on the role of HGs in acute lymphoblastic leukaemia (ALL), but very little has been done to understand their effects on acute myeloid leukaemia (AML). Materials and methods Through immunophenotyping, HGs were quantified in 471 BM samples from 292 postchemotherapy AML cases. These samples were analysed to determine whether there is any relationship between HGs percentages and French–American–British (FAB) subtypes or risk stratification of AML. Results HGs were identified in 57.75% of 471 patient samples (271) with a mean percentage of 3.87 ± 0.25%. No significant differences were found amongst different FAB subtypes of AML (P > 0.05). However, significant differences (P < 0.05) in HG numbers were noted between AML patients experiencing haematological complete remission (HCR) and those who have relapsed. HGs were identified in 59.9% of samples under HCR with a mean per cent of 3.98 ± 0.31%, and 36.7% of individuals who have relapsed have detectable HGs with a mean per cent of 1.75 ± 0.47. In addition, HGs in patients groups with low risk or intermediate risk were elevated when compared with high‐risk groups (P < 0.05), whilst no significant difference was found between low‐risk patients and intermediate‐risk patients (P > 0.05). Patients with >0.1% of HGs had a significantly better median leukaemia‐free survival (LFS) and overall survival (OS) than those with <0.1% of HGs (P < 0.01). Conclusions Therefore, our data indicate that HGs in bone marrow may be used as a favourable prognostic factor that predict for a better outcome of AML patients.